Reformation und Gegenwart Evangelisches Profil durch ein vierfaches "Allein"? - Munsonius, Hendrik (Universitätsverlag Göttingen, 2016)
The meaning of "reformatory theology" is often summarised by a number of "alone"-statements: Christ alone (solus Christus) by grace alone (sola gratia) through faith alone (sola fide) on the basis of the Scripture alone (sola scriptura). But can these terms express concisely what recent (Protestant) Christianity stands for? The articles look into this question from a systematic, historical and ecumenical perspective.